Oral microbiota transplantation fights against head and neck radiotherapy-induced oral mucositis in mice - Huiwen Xiao (Elsevier, 2021)
Oral mucositis is a common radiotherapy-induced complication among nasal, oral and laryngeal cancer (NOALC) patients. This complication leads to decreased quality of life and has few treatments. Here, fractionated radiation was performed to mimic radiotherapy for NOALCs in mouse models. Oral microbiota transplantation (OMT) mitigated oral mucositis, as judged by reconstructed epithelium and tongue papillae, fewer infiltrated leukocytes and more proliferative cells in the oral epithelium. The gut microbiota impacted oral mucositis progression, and OMT restructured oral and gut bacteria configurations and reprogrammed the gene expression profile of tongue tissues. In vivo silencing of glossal S100 calcium binding protein A9 debilitated the radioprotection of OMT. In light of clinical samples, we identified that patients with different alteration trends of Lactobacillaceae frequency presented different primary lesions and prognoses of NOALC following radiotherapy. Together, our findings provide new insights into the oral-gut microbiota axis and underpin the suggestion that OMT might be harnessed as a novel remedy to fight against oral mucositis in NOALC patients following radiotherapy in preclinical settings. Of note, oral microorganisms, such as Lactobacillaceae, might be employed as biomarkers to predict the prognosis of NOALC with radiotherapy.